ANALISIS KINERJA KEUANGAN DINAS PETERNAKAN DAN PERIKANAN KABUPATEN MUSI RAWAS - Herman Paleni (LPPM UNIVERSITAS BINA INSAN, 2017)
Regional Autonomy is the embodiment of government policies to encourage the improvement of services and public welfare in various aspects of life. . In supporting the implementation of regional autonomy, the availability of financial resources is certainly not small, if an area does not have sufficient or adequate funds, the region will not be able to implement the planned development program. But the size of the budget is certainly not a guarantee that the programs and activities that have been set in a certain period of time will be achieved. Principles and objectives of the transfer of financial management authority or government budget to the regions in a comprehensive manner so that regional finance can be managed in an orderly, law-abiding, efficient, economical, effective, transparent and responsible manner by paying attention to the principles of justice, compliance and benefits for the community.